2015
DOI: 10.1007/s10610-015-9275-9
|View full text |Cite
|
Sign up to set email alerts
|

Not All Substance Dependence Problems are Recognized as Risks—Comparing a Medical Health Study with Prison Assessments

Abstract: Substance abuse is viewed as one of the main factors (criminogenic needs) to be assessed and targeted in prison. Prison assessments of risk and needs are known to validly predict reoffending. However, there seems to be lacking research in how reliably the individual prisoner's problems, such as substance abuse, are represented in the assessments. In this study, we compare an independent medical health study (N=510) with in-prison assessments for the Eur J Crim Policy Res same persons to see whether some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…On the other hand, it has been reported that inmates with severe gambling problems do tend to seek help (Riley et al , 2017). The first step to making progress is, therefore, to identify the links between problem gambling and other life-control problems and then to integrate problem gambling treatment with prisons’ substance abuse treatment (Obstbaum et al , 2016) or broader prison rehabilitation programs. This would guarantee the best possible support services and treatment paths for this particular target population (Turner et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been reported that inmates with severe gambling problems do tend to seek help (Riley et al , 2017). The first step to making progress is, therefore, to identify the links between problem gambling and other life-control problems and then to integrate problem gambling treatment with prisons’ substance abuse treatment (Obstbaum et al , 2016) or broader prison rehabilitation programs. This would guarantee the best possible support services and treatment paths for this particular target population (Turner et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, according to MacAskill et al ( 2011) "alcohol problems among prisoners are under-detected, under-recorded and under-treated". The screening may be restricted to a yes/no-question (Parkes et al 2011) or to few unvalidated items (Obstbaum et al, 2016). The failure to use standardized assessment tools is staggering, but three-or four-item screeners are feasible and probably more acceptable than more time-consuming alternatives.…”
Section: Implications and Suggestions For Further Researchmentioning
confidence: 99%
“…It would be crucial to better recognize problem gambling in these risk and needs assessments. Screening and support for gambling problems should be organized and integrated into prisoner health care (Obstbaum et al 2016).…”
Section: Confidence In Ability To Provide Services and Needs For Contmentioning
confidence: 99%